AN EMPIRICAL STUDY ON NEEDS ANALYSIS OF BUSINESS ENGLISH COURSE - Ruliq Suryaningsih (INOVISH JOURNAL, 2021)
This study investigated the English language needs for business English course for the student of the Islamic banking department. It is important to conduct the research to decide the appropriate materials that suitable for the students' future career that is a bank employee. The informants included the managerial and staff-level employees in banking sectors, the vice dean for Academic of Islamic Economic and Business Faculty of IAIN Ponorogo, the head of Islamic banking department of IAIN Ponorogo, Business English lecturer, and some students of business English course. This research employs a qualitative approach. Through interviews and questionnaires, the finding of the research revealed that all of the informants suggested that the material should be beneficial for students’ future careers as bank employees. To make the teaching and learning process more effective, lecturers must pay attention not only to the selection of the right material, but also related to students’ learning preference.